2010
DOI: 10.1038/oby.2009.432
|View full text |Cite
|
Sign up to set email alerts
|

Changes in School Environments With Implementation of Arkansas Act 1220 of 2003

Abstract: INTRODUCTIONObesity is rapidly becoming one of the most critical health threats facing the United States. Rates of obesity among adults and children have increased at an alarming rate over the past four decades. Currently, 63% of US adults (1) and more than 33% of children and adolescents (2) may be classified as overweight or obese. The short-and long-term health implications of this epidemic are being considered with alarm by health professionals and policy experts. Among adults, obesity is linked to cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 14 publications
4
51
0
Order By: Relevance
“…Past evaluations of laws or policies to improve PE have found some positive impacts [39,40], but these assessments in LAUSD contribute to the evidence that a more recent focus on standardized testing outcomes and budgetary constraints due to the economic downturn may be hindering the implementation of newer state or district policies aimed at improving PE. A more recent evaluation of school-based childhood obesity policies in Tennessee and Mississippi ending in 2009 that included observations on school sites found that funding constraints and prioritization of standardized test scores over PE negatively impacted policy implementation [41].…”
Section: Discussionmentioning
confidence: 93%
“…Past evaluations of laws or policies to improve PE have found some positive impacts [39,40], but these assessments in LAUSD contribute to the evidence that a more recent focus on standardized testing outcomes and budgetary constraints due to the economic downturn may be hindering the implementation of newer state or district policies aimed at improving PE. A more recent evaluation of school-based childhood obesity policies in Tennessee and Mississippi ending in 2009 that included observations on school sites found that funding constraints and prioritization of standardized test scores over PE negatively impacted policy implementation [41].…”
Section: Discussionmentioning
confidence: 93%
“…[49][50][51][52][53] We also encourage future studies to examine whether students who reside in states with particularly stringent standards (eg, lower limits on fat or sugar content) experience less BMI change. Few states had such stringent standards in 2003, prohibiting us from using stricter criteria to define strong laws.…”
Section: Discussionmentioning
confidence: 99%
“…These data, as well as historical data from the US Centers for Disease Control and Prevention's state School Health Profiles (32) study, the School Health Policies and Programs Study (33,34) and USDA's SNDA-III (14) , support the view that the inconsistent approach to regulating competitive foods in schools needs improvement. The inconsistent approach to restricting competitive foods in schools has not led to universal changes in the availability of such foods nationwide, although several studies have demonstrated that state laws do affect student consumption and access to less healthful foods and beverages such as whole milk, sugar-sweetened beverages and high-fat/salty snacks (35)(36)(37)(38)(39) . And there is emerging, albeit mixed, evidence of the impact of state and/or district competitive food policies on BMI (40)(41)(42)(43)(44)(45) .…”
mentioning
confidence: 99%
“…And there is emerging, albeit mixed, evidence of the impact of state and/or district competitive food policies on BMI (40)(41)(42)(43)(44)(45) . Given that a number of studies (35)(36)(37)(38)(39)(45)(46)(47)(48)(49)(50)(51) have demonstrated strong competitive food and/or beverage policies can effectuate changes at the school level, it is expected that the availability of high-fat, high-energy, high-sugar foods and beverages in competitive venues will decline with nationwide standards governing competitive foods and beverages.…”
mentioning
confidence: 99%